2016
DOI: 10.3892/mmr.2016.5901
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a suppresses proliferation and induces apoptosis of human lens epithelial cells by targeting E2F3

Abstract: microRNA (miRNA) is abnormally expressed in numerous diseases, and it was intimately associated with cell proliferation and apoptosis. However, the mechanism by which miRNAs control cataractogenesis remains unclear. In the current study, it was demonstrated that miR-34a was highly expressed in the cataractous lens by stem-loop reverse transcription-quantitative polymerase chain reaction. Trying to investigate the role of miR-34a in human lens epithelial cells, miR-34a mimics were transfected into SRA01/04 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…24,25 Numerous studies have described the effect of miR-155 in regulating the progression of varied tumors. 26,27 There has been a trend to define miR-155 as a marker of solid and hematological malignancies for diagnosis and prognosis; 28 however, the exact role miR-155 plays in the occurrence and progression of NSCLC remains unknown. Therefore, illuminating the molecular mechanism in the occurrence and prognosis of NSCLC is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Numerous studies have described the effect of miR-155 in regulating the progression of varied tumors. 26,27 There has been a trend to define miR-155 as a marker of solid and hematological malignancies for diagnosis and prognosis; 28 however, the exact role miR-155 plays in the occurrence and progression of NSCLC remains unknown. Therefore, illuminating the molecular mechanism in the occurrence and prognosis of NSCLC is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, regulating RNAs that control gene expression has raised increasing attention in various situations. Although the role of microRNAs (miRNAs) in lenses is well established, 26 , 27 the role of lncRNAs in lens development and cataracts is still poorly understood. With previous studies reporting the existence of lncRNAs in lens development, 18 , 19 , 20 novel lncRNA ALB is the first, to our knowledge, to potentially play a role in human lens development.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no effective drug to treat cataract, so we need to find targeted drugs. While miR-34a has been found to have an effect on human lens epithelial cells, making its pathogenesis in cataract an important research direction (13). In this study, the expression of miR-34a in cataract rats and its related mechanism were studied through a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 plays an important role in the self-renewal and aging of eye stem cells and is associated with various age-related eye diseases. In human eyes, gene expression of SIRT1 in lens epithelium and retina of senile cataract patients has been detected (13,14). Studies have revealed that miR-34a can inhibit the expression of SIRT1, and SIRT1 can upregulate the expression of Nrf2 and activate the Nrf2/antioxidant response element (ES) pathway to protect cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%